2017
DOI: 10.1038/s41598-017-07722-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of placental cord drainage in the third stage of labour: A meta-analysis

Abstract: Observational studies have demonstrated that placental cord drainage can shorten the length of the third stage of labour and reduce blood loss during vaginal deliveries. The aim of our work was to evaluate the existing evidence for the effectiveness of placental cord drainage in the third stage of labour. PubMed, Embase, the Cochrane Library, Web of Science, Google Scholar and 50 journals were searched up to the 4th of June, 2017. Randomized controlled trials comparing placental cord drainage with no cord drai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…A recent meta-analysis including 9 studies and 2653 patients found that the duration of third stage of labor is shortened (2,28 minutes) although blood loss was the same [ 28 ]. A new finding was the reduction of 3% in postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis including 9 studies and 2653 patients found that the duration of third stage of labor is shortened (2,28 minutes) although blood loss was the same [ 28 ]. A new finding was the reduction of 3% in postpartum hemorrhage.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis also showed that for women with normal vaginal deliveries, the occurrence of postpartum hemorrhage was reduced by 3%. The authors concluded that placental cord drainage is a simple and non-invasive procedure that should be considered after delayed cord clamping [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cord drainage shortens the duration of the third stage of labor; this method appears to be safe and does not increase postpartum complications [15]. Observational studies have shown that umbilical cord drainage can shorten the duration of the third stage and reduce blood loss during vaginal delivery [16]. Placental drainage of fetal blood before spontaneous placental delivery at the time of cesarean delivery significantly reduces the incidence of fetomaternal transfusion [17].…”
Section: Discussionmentioning
confidence: 99%